Association between intake of flavanones and the overweight/obesity and central obesity in children and adolescents: a cross-sectional study from the NHANES database - Liu, Yangyang; Liu, Zhuoqiong; Wu, Nan (Frontiers in Nutrition, 2024)
The prevalence of obesity (Ob), overweight (Ow) and central obesity (CO) in children and adolescents has increased dramatically over the past decades globally.Flavanones have been recently studied as adjuvants for the treatment of obesity. This study was aimed at evaluating the association between intake of flavanones and its subclasses and the Ow/Ob and CO in children and adolescents.Methods: This cross-sectional study extracted the data of children and adolescents with Ow/Ob and CO from the National Health and Nutrition Examination Survey (NHANES) database for 2007-2010 and 2017-2018. Ow and Ob were defined as a body mass index (BMI) ≥ 85 th percentile. CO was defined as a waist circumference (WC) ≥ 90th percentile. The association between intake of flavanones and its subclasses and the Ow/Ob and CO in children and adolescents was determined by weighted univariate and multivariate Logistic regression models adjusted for potential covariates, and odds ratios (ORs) with 95% confidence intervals (CIs) was calculated. To further explore association between intake of flavanones and its subclasses and the Ow/Ob and CO in children and adolescents, subgroup analyses stratified by age, and gender.Of the total 5970 children and adolescents, 2463 (41.2%) developed Ow/Ob and 1294 (21.7%) patients developed CO. High intake of flavanones, eriodictyol, hesperetin, and naringenin were associated with lower odds of Ow/Ob in children and adolescents. (OR: 0.75, 95%CI: 0.62-0.92, OR: 0.69, 95%CI: 0.55-0.87, OR: 0.69, 95%CI: 0.55-0.87, and OR: 0.76, 95%CI: 0.63-0.92, respectively). In addition, high intake of flavanones, eriodictyol, and naringenin were associated with lower odds of CO in children and adolescents (OR: 0.71, 95%CI: 0.57-0.88, OR: 0.67, 95%CI: 0.51-0.86, and OR: 0.69, 95%CI: 0.55-0.86, respectively). Subgroup analyses showed that among all the different subgroups, high intake of flavanones was associated with lower odds of Ow/Ob and CO in children and adolescents.A diet loaded with high flavanones were associated with lower odds of Ow/Ob and CO in children and adolescents, and children and adolescents should be encouraged to increase their intake of flavanones.